Предмет: Алгебра,
автор: АфнасийНикитн45646
Преобразуйте выражение: (4x-4)*(x+1)-(2x+3)
Ответы
Автор ответа:
0
4x^2 + 4x - 4x - 4 - 2x - 3 = 4x^2 - 2x - 7
Автор ответа:
0
4(x-1)(x+1)-(2x+3)=0
4(x²-1)-(2x+3)=0
4x²-4-2x+3=0
4x²-2x-1=0
Дальше только найти дискриминант и корни уравнения. Это, я думаю, и сам сможешь ;)
4(x²-1)-(2x+3)=0
4x²-4-2x+3=0
4x²-2x-1=0
Дальше только найти дискриминант и корни уравнения. Это, я думаю, и сам сможешь ;)
Похожие вопросы
Предмет: Английский язык,
автор: versache36
Предмет: Алгебра,
автор: aslankakakaff
Предмет: Математика,
автор: fridhivebrsv
Предмет: Математика,
автор: kristina0903
Предмет: Математика,
автор: adosymkhanova